2016
DOI: 10.1111/deci.12243
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Effects of the Privacy‐Handling Management Styles of Social Networking Sites on User Satisfaction: A Conflict Management Perspective

Abstract: The issue of consumer information privacy, arguably the most substantial and persistent problem confronting e‐commerce companies in general and online social networking service providers in particular, often results in unsatisfied customers. Researchers have investigated privacy from various perspectives and in a multitude of settings, yet there have been few attempts to understand privacy versus satisfaction, particularly from the perspective of conflict management. Because users’ privacy can be negatively af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 90 publications
0
20
0
Order By: Relevance
“…Future studies could further explore the strategies for conflict resolution. For example, Zhang et al (2017) proposed four types of conflict management strategies: problem-solving, accommodating, asserting and avoiding. The authors confirmed the effects of these strategies on privacy issues in the context of SNS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future studies could further explore the strategies for conflict resolution. For example, Zhang et al (2017) proposed four types of conflict management strategies: problem-solving, accommodating, asserting and avoiding. The authors confirmed the effects of these strategies on privacy issues in the context of SNS.…”
Section: Discussionmentioning
confidence: 99%
“…In this research, information security–related conflicts are defined as the stimuli that affect internal states. “Conflict” describes a process in which one party perceives that its interests are being opposed or negatively affected by another party (Zhang et al , 2017). Conflict arises among interdependent parties that perceive incompatible interests or goals when they interact.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…financial, social, performance and prosecution risks) to be lower. Zhang et al (2018) also suggested that people with high optimism bias may believe they have greater control over the outcome, therefore, they perceive low privacy risks. Applied here we postulate that e-waste owners high in optimism bias may under-weigh information risks; even if the risk is judged to be high, it will not influence coping intentions as the risk will only marginally be integrated into one's mental calculus.…”
Section: Research Model and Hypothesis Developmentmentioning
confidence: 99%
“…Nowadays, both primary survey data and secondary data directly crawled from social networking sites have been used by the researchers. Both Chakraborty et al (2013) and Zhang et al (2017) studied social media users’ behavioral responses related to privacy issues of the users. Chakraborty et al (2013) used data from Facebook pages of profiles of elderly adults to study their privacy-preserving actions.…”
Section: Data Collection and Data Types In Social Media Researchmentioning
confidence: 99%
“…Chakraborty et al (2013) used data from Facebook pages of profiles of elderly adults to study their privacy-preserving actions. Zhang et al (2017), on the other hand, used data from the online surveys of respondents who use social networking sites. Amazon Mechanical Turk was used to recruit respondents (social media users).…”
Section: Data Collection and Data Types In Social Media Researchmentioning
confidence: 99%